Rare Case of Acute Pancreatitis Presenting With ST-Segment Elevation - Kristy Leker MD, MPH; Parampreet Johal MBBS (Journal of Investigative Medicine High Impact Case Reports)
When first presented, ST-segment elevation on EKG (electrocardiogram) requires close scrutiny. The most concerning of possible diagnoses is acute coronary syndrome, yet it is not the only clinical entity that can cause ST-segment elevation. Herein, we present a case of a 62-year-old male current smoker with past medical history of uncontrolled diabetes, hypertension, and hyperlipidemia presenting with abdominal pain for 1 week duration. His initial admission EKG illustrated ST-segment elevation; however, his clinical presentation, lack of anginal symptoms, normal bedside transthoracic echocardiogram, and normal range troponin were not indicative of myocardial infarction. In fact, he was found to have elevated lipase and CT findings consistent with acute pancreatitis. This case highlights an uncommon presentation of pancreatitis and illustrates the importance of obtaining a comprehensive clinical history when evaluating patients to ensure patient’s receive efficient and appropriate care.